ATTENUATION ANALYSIS ON FIBER TO THE HOME (FTTH) NETWORK WITH GIGABIT PASSIVE OPTICAL NETWROK (GPON) AT OXYGEN HOME PONTIANAK - Maulana, Fachri; Imansyah, Fitri; Marpaung, Jannus (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2023)
Optical fiber as a transmission medium that meets the needs of the internet with large bandwidth. The FTTH (Fiber To The Home) network can deliver a variety of digital information, such as voice, video and data more effectively so that it can support the Triple Play service marketed by Oxygen Home. To determine the feasibility and performance of the FTTH (Fiber To The Home) design system in the Bali Agung 2 Complex, South Pontianak, it will be assessed based on test parameters. The test parameters are Power Link Budget for system feasibility and BER (Bit Error Ratio) will be displayed with an eye diagram for system performance used using Optisystem software, Optisystem is software that can be used to simulate a fiber optic network from central to end – user. From the results of the FTTH network simulator using optical system software, it is found that the farthest user attenuation value is Prx: -16.018 dBm, 1.4804 x 10-61 and Q factor 16.5122. The results obtained are feasible because they are above the minimum FTTH network standard with GPON technology